A Phospholipid-Protein Complex from Krill with Antioxidative and Immunomodulating Properties Reduced Plasma Triacylglycerol and Hepatic Lipogenesis in Rats - Marie S. Ramsvik (Marine Drugs, 2015)
Dietary intake of marine omega-3 polyunsaturated fatty acids (n-3 PUFAs) can change the plasma profile from atherogenic to cardioprotective. In addition, there is growing evidence that proteins of marine origin may have health benefits. We investigated a phospholipid-protein complex (PPC) from krill that is hypothesized to influence lipid metabolism, inflammation, and redox status. Male Wistar rats were fed a control diet (2% soy oil, 8% lard, 20% casein), or diets where corresponding amounts of casein and lard were replaced with PPC at 3%, 6%, or 11% (wt %), for four weeks. Dietary supplementation with PPC resulted in significantly lower levels of plasma triacylglycerols in the 11% PPC-fed group, probably due to reduced hepatic lipogenesis. Plasma cholesterol levels were also reduced at the highest dose of PPC. In addition, the plasma and liver content of n-3 PUFAs increased while n-6 PUFAs decreased. This was associated with increased total antioxidant capacity in plasma and increased liver gene expression of mitochondrial superoxide dismutase (Sod2). Finally, a reduced plasma level of the inflammatory mediator interleukin-2 (IL-2) was detected in the PPC-fed animals. The present data show that PPC has lipid-lowering effects in rats, and may modulate risk factors related to cardiovascular disease progression.